Corporate Governance Rules and Insider Trading Profits - Cziraki, Peter; De Goeij, Peter; Renneboog, Luc (Review of Finance, 2014)
Abstract We investigate patterns of abnormal stock performance around insider trades on the Dutch market. Listed firms in the Netherlands have a long tradition of limiting shareholders’ rights. Using a change in corporate governance regulations as a natural experiment, we show that governance rules have a causal effect on insider trading profits. Our results imply that insider transactions are more profitable at firms where shareholder rights are not restricted by antishareholder mechanisms. These findings are inconsistent with internal monitoring of insider trading. Rather, we explain this empirical pattern by imperfect substitution between insider trading profits and other private benefits of control.